2020
DOI: 10.3389/fcvm.2020.00115
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Converting Enzyme Inhibitors (ACEIs) Decrease the Progression of Cardiac Fibrosis in Rheumatic Heart Disease Through the Inhibition of IL-33/sST2

Abstract: Rheumatic heart disease (RHD) is common in developing countries and poses a big medical challenge and burden. The pathogenesis of RHD is influenced by the triad of host, agent, and environment. Autoantigens generated from Group A Streptococcus (GAS) infection are captured by the resident dendritic cells (DCs) in the heart's valvular endothelium. DCs differentiate into antigen presenting cells (APC) in the valve interstices. APC induces activation of autoreactive T cells, which triggers inflammation and tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 82 publications
(108 reference statements)
0
29
0
Order By: Relevance
“…Second, in this study we discovered for the first time that RDN protected the failing heart via the modulation of IL-33/ST2 signaling, yet the detailed mechanism is still unclear. Existing studies have found that changes in IL-33/ST2 pathway are associated with the RAAS system (43,44). Since RAAS is regulated by RDN, we speculate that RDN may exert a cardioprotective effect on IL-33/ST2 pathway through RAAS and further detailed mechanisms are under exploration.…”
Section: Discussionmentioning
confidence: 78%
“…Second, in this study we discovered for the first time that RDN protected the failing heart via the modulation of IL-33/ST2 signaling, yet the detailed mechanism is still unclear. Existing studies have found that changes in IL-33/ST2 pathway are associated with the RAAS system (43,44). Since RAAS is regulated by RDN, we speculate that RDN may exert a cardioprotective effect on IL-33/ST2 pathway through RAAS and further detailed mechanisms are under exploration.…”
Section: Discussionmentioning
confidence: 78%
“…Angiotensin II was shown to promote IL-33 and ST2L expression by stimulating transforming growth factor (TGF)-β to induce fibrosis in RHD while angiotensin-converting enzyme inhibitor inhibited the production of angiotensin II, which in turn promoted the binding of IL-33 to ST2L and alleviated cardiac fibrosis. 70 Thus, IL-33 and ST2L might play a protective role in RHD. In patients with ADHF, elevated sST2 correlates directly with ADHF severity, and powerfully and independently predicts an increased risk of heart failure complications including arrhythmia, pump failure, and death.…”
Section: Role Of Il-33 In Cardiac Diseasementioning
confidence: 99%
“…The inhibition of angiotensin II by angiotensin converting enzyme inhibitors reduces the inflammatory response and the level of sST2. In the absence of sST2, IL-33 interacts with ST2L [ 109 ]. Moreover, in vitro studies have shown that angiotensin II treatment significantly elevated the level of circHIPK3 in the cardiac fibroblasts and surrounding heart tissue.…”
Section: Anti-fibrotic Therapiesmentioning
confidence: 99%